Local government Third edition Policy and management in local authorities - Howard Elcock (by Routledge, 1994)
Now that it is into its third edition, this book has come to resemble my grandfather’s axe, of which my father replaced the blade and I replaced the handle. The years since Local Government was first published in 1982 have been a period of tremendous instability for local government. On the one hand, it has been under sustained attack by the successive Conservative administrations which have held power since 1979. On the other hand, the ‘new urban Left’ brought a period of stimulating development of new policies, especially in economic development and equal opportunities, during the 1980s. The increased variation and experimentation with local authority management processes and structures which developed after reorganisation in 1974–1975 in Scotland—has continued to develop apace, with the result that it is now even more difficult to generalise about local authorities’ policy-making and management structures and processes than it was a decade ago. The internal decentralisation initiatives of the 1970s and 1980s; the imposition first of compulsory competitive tendering on a widening range of services and then of the community care scheme, have presented local authorities with a new range of management challenges, to which they have responded in varying ways. Financial pressure has forced local authorities to review their budgetary processes and has produced major conflicts between the Government and individual local authorities, notably Liverpool City Council and Lambeth Borough council.